Nutritional status of children in districts of Haryana an analysis from National Family Health Survey (NFHS-4 and 5) - Singhal, Parul; Ohlan, Sunny; Singh, Sandeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Malnutrition in early life either undernutrition or particularly obesity, can be the underlying cause of many non‐communicable diseases. Nowadays child growth failure phenomena are an enduring public health concern in lower and middle-income countries like India. DBM (Double burden of malnutrition) that is underweight and overweight is also a global concern. Recently, National Family Health Survey (NFHS-5) 2019-21 of India, data reported that 35.5 % of children age less than 5 years are stunted or they are too short for their age; 20% of children are too thin for their height (wasted) and 32% under 5 children are underweight. The district-level data of nutritional status of children indices were extracted from the district fact sheets of Haryana state, published by NFHS, India. This study is based upon two-time frames of the NFHS (NFHS-4 and NFHS-5) series. District wise change detection of nutritional status of children. Results found that the prevalence of stunted children is still present and increased in 4 districts of Haryana whereas wasted and underweight decreased from previous Survey in all districts of Haryana. As per data reported in the NFHS-5 fact sheet, there are 11 districts in Haryana which shows increased in overweight in children. This study may beneficial for health policy and program makers to understand the dynamic trends of changes in nutritional status of children of under 5 years of age group across the various districts of Haryana.